¿Qué hay de contemporáneo en lo contemporáneo?: metaficción y nomadismo en La hora de la estrella, de Clarice Lispector (Dossier Literatura brasileña y latinoamericana: cruce de lecturas) - Paredes, Lautaro (2025)
This paper analyzes the coordinates of contemporaneity in A Hora da Estrela by Clarice Lispector, as well as the possibility of reading the novel through the lens of Latin American historical and cultural processes. The study involves a detailed examination of how the categories commonly used by literary criticism to define contemporary literature (metafiction, autofiction, intertextuality, etc.) operate within the text. These categories are further expanded and challenged through concepts such as post-autonomy, cosmopolitan literatures, and national literatures, as discussed in Aquí América Latina by Josefina Ludmer. Finally, the article explores how certain current notions from the Humanities and Literary Studies—such as nomadism, geographic representation, and mixed identities—offer productive frameworks for understanding the novel, its characters, and its unique expression of the contemporary.